Cutting through the value chain: The long-run effects of decoupling the east from the west - Gabriel Felbermayr; Hendrik Mahlkow; Alexander-Nikolai Sandkamp (FIW - Research Centre International Economics, 2022)
With ever-increasing political tensions between China and Russia on one side and the EU and the US on the other, it only seems a matter of time until protectionist policies cause a decoupling of global value chains. This paper uses a computable general equilibrium trade model calibrated with the latest version of the GTAP database to simulate the effect of doubling non-tariff barriers - both unilateral and reciprocal - between the two blocks on trade and welfare. Imposing trade barriers almost completely eliminates bilateral imports. In addition, changes in price levels lead to higher imports and lower exports of the imposing country group from and to the rest of the world. The targeted country group increases exports to the rest of the world and reduces imports. Welfare falls in all countries involved, suggesting that governments should strive to cooperate rather than turning away from each other. By imposing a trade war on Russia, the political West could inflict severe damage on the Russian economy because of the latter's smaller relative size.
Keywords: F11; F13; F14; F17; 330; Trade; non-tariff barriers; global value chains; quantitative trade model; China; Russia; European Union